Penerapan Prinsip-Prinsip Pemerintahan yang Baik dalam Penyelenggaraan Pemerintahan - Putra Astomo (Kanun Jurnal Ilmu Hukum, 2014)
To run good governance must be based on making and implementing state policy which is democratic in the globalization era. This phenomenon is signed by the strength of social control toward the governance, while the phenomenon of it is signed by the dependency interstates, espectally in managing the economic resources and the activities of business. In order to succeed it the governance implementation and its principles must be ruled in it. Good Governance Principles in Running Governance